EFFECT OF CRYOPRESERVED PLACENTA EXTRACT ON SOME BIOCHEMICAL INDICES OF THERAPEUTIC EFFICIENCY AND TOXICITY OF DICLOFENAC SODIUM IN ADJUVANT-INDUCED EXPERIMENTAL ARTHRITIS - F. V. Hladkykh; M. O. Chyzh; A. O. Manchenko; I. V. Belochkіna; I. P. Mikhailova (Фармация и фармакология (Пятигорск), 2021)
Non-steroidal anti-inflammatory drugs are among the top requested ones in the clinic of internal medicine. However, these drugs are associated with a wide range of adverse reactions involving a number of organs and systems, in particular the gastrointestinal tract, cardiovascular system and kidneys.The aim of the study is to characterize the effect of the combined use of cryopreserved placenta extract and diclofenac sodium on the prooxidant-oxidative system, the activity of inflammatory, destructive and cytolytic processes, as well as protein and lipid metabolism in rats with experimental rheumatoid arthritis.Results. The administration of diclofenac sodium and cryopreserved placenta extract to rats with adjuvant arthritis normalized the level of active products of thiobarbituric acid and hence was indicative of the neutralization of an arthritis-induced oxidative stress. A statistically significant (p=0.01) increase of in a superoxide dismutase activity (by 30.6% relative as compared with rats of the control group) has also been established. An increase in the anti-inflammatory properties of diclofenac sodium in the combined use of diclofenac sodium with a cryopreserved placenta extract has been found out. The level of C-reactive protein decreased (p<0.001) by 61.1% as compared with the untreated rats, and the level of seromucoid has been significantly (p<0.01) decreased by 17.1% as compared with the rats of the monotherapy group treated with the studied NSAIDs. It was shown that alanine aminotransferase and aspartate levels were significantly lower (by 38.9%, p<0.01 and by 37.9%, p<0.01, respectively) as compared with those of the animals that had been administrated with diclofenac sodium. Their indices were by 16.7% (p=0.02) and 17.2% (p<0.001) lower than the indices of the control group rats with untreated adjuvant arthritis. The established changes of aminotransferases levels indicate the ability of a cryopreserved placenta extract to level not only an arthritis-induced cytolytic syndrome, but also a diclofenac-induced one. The combined use of cryopreserved placenta extract and diclofenac sodium was accompanied by the normalization of the total lipids level and phospholipids in the blood serum of rats against the background of experimental rheumatoid arthritis. Thus, the content of phospholipids in the lipid pool statistically significantly (p=0.02) increased by 22.6% as compared with the indices of the animals with adjuvant arthritis without treatment.Conclusion. The study showed that the combined use of diclofenac sodium and cryopreserved placenta extract leads to the restoration of the balance of the prooxidant-antioxidant system that is more pronounced than monotherapy with diclofenac sodium. A decrease in the activity of inflammatory, destructive and cytolytic processes, as well as the restoration of lipid metabolism in the rats with experimental rheumatoid arthritis, has also been observed.